Diagnostic Performance of Anti-Müllerian Hormone, Luteinizing Hormone to Follicle-Stimulating Hormone Ratio, Testosterone, and Prolactin to Predict Polycystic Ovary Syndrome Among Sudanese Women - Alhassan S; Elmugadam A; Elfadil GA; Abubaker N; Elfaki EM; Hamza A; Abdalhabib EK; Karar T (Dove Medical Press, 2023)
Samia Alhassan,1 Abdelgadir Elmugadam,1 Ghada A Elfadil,1 Nuha Abubaker,1 Elyasa M Elfaki,2 Alneil Hamza,2 Ezeldine K Abdalhabib,2 Tarig Karar3,4 1Department of Clinical Chemistry, College of Medical Laboratory Science, Sudan University of Science and Technology, Khartoum, Sudan; 2Department of Clinical Laboratory Sciences, College of Applied Medical Sciences, Jouf University, Al-Qurayyat, Saudi Arabia; 3Clinical Laboratory Sciences Department, College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 4King Abdullah International Medical Research Centre, Riyadh, Saudi ArabiaCorrespondence: Elyasa M Elfaki, Department of Clinical Laboratory Sciences, College of Applied Medical Science, Jouf University, Omer bin Alkhattab Street, Al-Qurayyat, 77452, Saudi Arabia, Tel +966500769479, Email eelfaki@ju.edu.saBackground: Polycystic ovary syndrome (PCOS) is one of the most important contributing factors to infertility. The diagnosis of PCOS is not an easy procedure, as the signs and symptoms are heterogeneous and of undefined etiology. There are only a few published studies that address the diagnostic performance of anti-Müllerian hormone in diagnosis of PCOS in sub-Saharan Africa including Sudan.Objective: This study aims to assess anti-Müllerian hormone (AMH), luteinizing to follicle-stimulating hormone ratio (LH: FSH), total testosterone (TT), and prolactin (PRL) levels among PCOS. In addition, we determine if AMH can be used as a predictor of PCOS among Sudanese women.Methods: There were 600 women enrolled in this observational cross-sectional study, 300 of whom had PCOS, and 300 of whom healthy women; PCOS was diagnosed using the Rotterdam criteria. On days 2- 4 of the menstrual cycle, serum LH, FSH, AMH, TT, and PRL levels were measured for all participants. Diagnostic performance of these parameters for PCOS was determined by receiver operating characteristic (ROC) curve.Results: Significantly higher means among PCOS regarding their BMI, AMH; LH: FSH ratio; TT; PRL, whereas significantly inverse in FSH compared with normal ovulatory women. On ROC analysis, AMH had the largest operating characteristic curve at cut-off > 3.95 ng/mL; AUC = 0.999 with Youden's index 0.99%, followed by LH: FSH ratio at cut-off 0.749; AUC=0.932; Youden's index 0.813%, TT cut-off 0.82 mIU/L, AUC=0.852 with Youden's index 0.58, while PRL showed the lowest AUC=0.627 with cut-off 15.3 ng/mL, Youden's index was 0.18%, P. value< 0.001.Conclusions: Sudanese women with PCOS had higher serum AMH level, LH:FSH ratio, and TT level. Moreover, AMH level has better discriminative power and good diagnostic potency for the diagnosis of PCOS among Sudanese.Keywords: PCOS women, AMH, LH:FSH ratio, TT, PRL, Sudan